Sejarah Teknik Pengobatan Kuno India (Ayurveda) - imamatul azizah azizah; Riska Syafitri; Umy Kalsum (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2020)
This article was written through a literature review, aimed at explaining Ayurveda, which is one of the ancient medical techniques in medicine that originated in India. Where until now its role remains with the use of this treatment technique as well as ancient or ayurvedic treatment techniques that also contribute to the development of world medical science. Overall this article discusses material relating to the history of medical science in general, relating to the science of medicine that spreads throughout regions of the world both Arabic, Chinese or Indian itself. Then in this article also contains a discussion of the introduction of ancient Indian or Ayurved treatment techniques, What is Ayurved. It also explained the techniques of treatment in healing patients in Ayurved.